Analisis perkembangan moral anak melalui pembelajaran aqidah akhlak di MI MA’ARIF Candran - Seka Andrean; Maemunah Maemunah (Latifah Pres, 2020)
Learning activities performed by teachers should be able to create a fun and efficient teaching and learning atmosphere. On the other hand, learning activities are also required to be directed to the moral development of a child in order to have a good personality. This training aims to determine the moral development of the child through the study of the sexual Aqidah in MI Ma'arif Candran. The subject of this study was the students and teachers of MI Ma'arif Candran. The approach used in this research is a qualitative approach, using a descriptive method. The results of this study showed that in the moral development of the child through the study of sexual Aqidah implemented by the teacher at MI Ma'arif Candran is to develop a learning plan that adjusts to the situation, the characteristics of students and the potential of students by using methods and strategies consisting of: Habituation methods, methods of ethics, methods of advice, control mechanisms, and sanctions.